2016
DOI: 10.1038/ncomms11762
|View full text |Cite
|
Sign up to set email alerts
|

Stromal senescence establishes an immunosuppressive microenvironment that drives tumorigenesis

Abstract: Age is a significant risk factor for the development of cancer. However, the mechanisms that drive age-related increases in cancer remain poorly understood. To determine if senescent stromal cells influence tumorigenesis, we develop a mouse model that mimics the aged skin microenvironment. Using this model, here we find that senescent stromal cells are sufficient to drive localized increases in suppressive myeloid cells that contributed to tumour promotion. Further, we find that the stromal-derived senescence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
305
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(314 citation statements)
references
References 52 publications
7
305
0
2
Order By: Relevance
“…Both aging 92,93 and obesity 94 have been reported to produce a proinflammatory state and to lead to an increase in the number of suppressive immature myeloid cells in circulation. Moreover, sex hormones may lead to altered TIME responses in male as compared with female patients, because estrogen has been shown to activate the STAT3 pathway in human and mouse bone marrow myeloid progenitor cells, thereby leading to an increased presence of potentially suppressive myeloid cells in circulation 95 .…”
Section: The Contribution Of Systemic Factors To the Timementioning
confidence: 99%
“…Both aging 92,93 and obesity 94 have been reported to produce a proinflammatory state and to lead to an increase in the number of suppressive immature myeloid cells in circulation. Moreover, sex hormones may lead to altered TIME responses in male as compared with female patients, because estrogen has been shown to activate the STAT3 pathway in human and mouse bone marrow myeloid progenitor cells, thereby leading to an increased presence of potentially suppressive myeloid cells in circulation 95 .…”
Section: The Contribution Of Systemic Factors To the Timementioning
confidence: 99%
“…The SASP can also promote tumour growth by establishing an immunosuppressive microenvironment (Toso et al 2014, Ruhland et al 2016. It was previously shown that temporary and selective inactivation of tumour suppressor PTEN could induce hyperactivation of a signalling pathway that led to senescence (Alimonti et al 2010).…”
Section: :9mentioning
confidence: 99%
“…These studies demonstrate the importance of suppressing immune surveillance of senescent tumour cells engendered by drug treatments. On a related note, a recent report (Ruhland et al 2016) showed that senescent stromal cells were sufficient to create an immunosuppressed environment. Here, stromal-derived SASP factor IL-6 recruited suppressive myeloid cells and inhibited anti-tumour T-cell response.…”
Section: :9mentioning
confidence: 99%
“…Of the publications that do address how senescent stromal cells influence tumor growth in vivo , only one has been conducted in an immune-proficient mouse model (12). Consequently, mechanisms by which paracrine SASP signals emanating from the senescent tumor stroma might alter malignant cell clearance by the immune system are understudied—a particularly pertinent point given increasing interest in combining established treatment modalities ( i.e .…”
Section: Introductionmentioning
confidence: 99%